MODERN TRENDS IN QUALITY MANAGEMENT OF SERVICES OF EDUCATIONAL INSTITUTIONS - SHPYLOVA, Vira; DESIATOV, Tymofii; SPIIAN, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Quality management of educational services is one of the key areas of improvement of the education system in the context of growing social requirements and integration into the world educational space. The quality of educational activities directly affects the competitiveness of educational institutions, the level of professional training of specialists and the innovative development of the state. In the current conditions of digitalization, globalization and socio-economic transformations, the need to implement effective quality management mechanisms focused on international standards and principles of sustainable development of education is increasing. The rapid development of educational services necessitates the provision of educational institutions with a high level of flexibility and adaptability, as well as the introduction of modern methods of quality management, which provides for the integration of internal control systems with innovative models of the organization of the educational process. This necessitates a scientific study of modern trends in the management of the quality of educational services as a prerequisite for increasing the efficiency of educational activities and the formation of competitive advantages in the national and international educational space. The main purpose of the study is to identify and scientifically substantiate modern trends in the management of the quality of services of educational institutions, as well as to identify effective mechanisms and practical tools that can ensure an increase in the effectiveness of the educational process and the competitiveness of educational institutions in the context of globalization and digital transformation. Under the conditions of intensive globalization integration and digital transformation, the issue of quality management of services of educational institutions is becoming especially relevant. The educational process is perceived not only as a social structure aimed at forming the intellectual and cultural potential of society, but also as an important area of national competitiveness. That is why the management of the quality of educational services is becoming a key factor in ensuring the sustainable development of society and the integration of the national educational system into the world educational space. Current trends in this area involve the transition from formal control to a systematic approach, which includes strategic planning, the introduction of digital technologies and innovative teaching methods, the development of inclusiveness and academic integrity, active interaction with stakeholders, as well as a focus on international quality standards. Such an integrated approach ensures an increase in the efficiency of the educational process, contributes to the adaptation of graduates to the needs of the global labor market and forms the innovative potential of educational institutions. Modern trends in the management of the quality of services of educational institutions are characterized by high complexity, consistency and integration of innovative approaches, which provide not only strategic planning and digitalization of processes, but also ensuring inclusiveness, academic integrity and the formation of a corporate culture of quality. They are aimed at harmonizing the internal standards of institutions with international requirements, adapting educational programs to the needs of the globalized labor market and strengthening the competitiveness of graduates, which is becoming an important criterion for the effectiveness of educational activities. The identified characteristic features of modern management demonstrate a gradual transition from traditional, formal quality control to a systematic, integrated approach that covers the interaction of all components of the educational process. This approach allows you to combine the internal resources of the institution, the pedagogical potential of teachers, the expectations of students and the requirements of employers, as well as take into account external challenges related to legislative changes, digitalization of education and globalization of the educational environment.